Incentives to Open Access: Perspectives of Health Science Researchers - Carmen López-Vergara; Pilar Flores Asenjo; Alfonso Rosa-García (Publications, 2020)
Technological development has transformed academic publication over the past two decades and new publication models, especially Open Access, have captured an important part of the publishing market, traditionally dominated by the Subscription publication model. Although Health Sciences have been one of the leading fields promoting Open Access, the perspectives of Health Science researchers on the benefits and possibilities of Open Access remain an open question. The present study sought to unveil the perspective of researchers on scientific publication decisions, in terms of the Subscription and Open Access publication model, Gold Road. With this aim, we surveyed Spanish researchers in Health Sciences. Our findings show that the value of publishing in Open Access journals increases as the experience of the researcher increases and the less she/he values the impact factor. Moreover, visibility and dissemination of the results are the main determinants of publication when choosing an Open Access journal as the first option. According to the response of the researchers, the reduction of fees and the increase in financing are important economic incentive measures to promote the Open Access publication model. It is widely accepted that the volume of Open Access publications will increase in the future.